Domain-Specific Seed Removal for Biomedical Image Segmentation using SICLE - Kochem, Fábio F.; Belém, Felipe; Falcão, Alexandre X.; P. Jr., Zenilton K. G. do; Guimarães, Silvio Jamil F. (Anais Estendidos da Conference on Graphics, Patterns and Images (SIBGRAPI), 2025)
Superpixels through Iterative CLEarcutting (SICLE) is an efficient framework for image segmentation that operates on an iterative principle of seed removal to refine the final result. While effective for general purposes, its reliance on standard seed removal criteria limits its performance in specialized domains. This is particularly evident in biomedical analysis, where the goal is often to isolate a single object of interest using a low number of superpixels, a task where generic criteria often fail. To address this limitation, this work proposes two seed removal criteria: (i) a Position-Based Criterion that leverages prior anatomical knowledge to guide segmentation in medical images; (ii) a Color-Based Criterion specialized for identifying targets in pathological images based on their distinct color signature. By replacing generic heuristics with these domain-specific functions, we demonstrate that SICLE can be transformed into a more robust and specialized tool for targeted biomedical image analysis, significantly improving object delineation accuracy, including situations with a small quantity of superpixels.